Laparoscopic Assisted Percutaneous Anterior Gastropexy for the Management of Acute and Chronic Gastric Volvulus in Infants - Roberta Valentina Iacona; Francesco Grasso; Silvia Antonia Grimaldi; Massimo Lebet; Sebastiano Cacciaguerra (MDPI AG, 2022)
Acute and chronic gastric volvulus (ACGV) is a rare event in infants and children. Its prompt treatment is needed to avoid gastric ischemia and perforation. A laparotomy or a laparoscopic/endoscopic reduction with or without the gastrostomy formation has been described to treat this condition. We wanted to report our experience and describe the surgical technique used to perform the percutaneous laparoscopic assisted anterior gastropexy in neonates presenting with this condition. We perform a retrospective review of a single institution's experience with laparoscopic assisted percutaneous anterior gastropexy over a seven-year period (2015-2022). Procedures were performed under general anesthesia and the anterior gastropexy was performed using a modified extracorporeal knotting technique as described for the laparoscopic assisted repair of inguinal hernias via percutaneous internal ring suturing. Thirteen patients underwent surgery for ACGV at our institution over a seven-year period. The median age at diagnosis was 57 days, 7/13 patients presented with acute vomiting and regurgitation (54%), 1/13 (8%) presented with mainly feeding difficulties and 1/13 (8%) presented with acute abdominal distension. Data were not available for 4/13 patients. All of the patients underwent laparoscopic assisted anterior gastropexy using extracorporeal knotting technique; no gastrostomy insertion was needed. The median operative time was 50 min (40-95 min). No intraoperative complications were reported. Post-operatively patients were started on feeds on day 3 (2-5 days). Only one patient (8%) developed a postoperative complication: subcutaneous granuloma at the extracorporeal knot site. Although rare, acute GV is an important cause of gastric outlet obstruction with a detrimental outcome if not promptly recognized and treated. Laparoscopic assisted percutaneous anterior gastropexy is an attractive and safe alternative for the management of this condition in both infants and older children. This technique does not require gastrostomy placement and it has a very low morbidity rate with no mortality reported.